Validation and cut score’s estimation for the online learning scale using Item Response Theory (Journal of Applied Learning and Teaching, 2024)
This study aims to validate the Online Learning Scale (OLS) and estimate the OLS’s cut score. The sample was 1,459 undergraduate students across different universities and field studies in Thailand. The OLS was newly developed by synthesizing related literature, focus groups, and observations and was designed to measure online learning quality from student-centered perspectives. The 24 OLS items were validated using Classical Test Theory (CTT) and Item Response Theory (IRT). The OLS’ cut score was estimated by analyzing the scale’s lowest points of the test information function. The effectiveness of OLS’ cut score was investigated by dividing groups of samples by cut score and analyzing their difference using Chi-square test and ANOVA with other variables. The results indicated that the OLS showed appropriate psychometric properties: 1) The Cronbach’s alpha reliability was .94 and discrimination indices were .62 to .79, 2) CFA fit indices indicated good fit (CFI = .953, RMSEA = .053), and 3) The IRT difficulty parameters were arranged in order and in the range of -3.0 to 3.0, while the discrimination parameters exceeded 0.65 in all items. The estimated two cut scores (29 and 48 points) effectively distinguished the online learning quality delivered to the students.